User Acceptance Test pada Media Pembelajaran Interaktif Pengenalan Huruf Alfabet Menggunakan Metode ADDIE - Alfian, Ari Nurul; Ayu Utami, Tri; Apriani, Rika; Ismiyana Putri, Dwi (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management; Vol 10 No 1 (2025): INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS (JUNI 2025)DO - 10.51211/imbi.v10i1.3384, 2025)
This research aims to develop and implement interactive learning media for recognizing alphabet letters at the early childhood education level, especially at Al-Izzah Cibarusah IT. The method used is ADDIE which involves the stages of needs analysis, design, development, implementation and evaluation of learning media. The resulting learning media is an interactive application designed to help children understand and remember the letters of the alphabet in a fun and effective manner. The implementation of learning media was carried out at Al-Izzah Cibarusah IT to measure its effectiveness and usefulness in the actual learning context. Evaluations are carried out to evaluate student responses, the performance of learning media, and their impact on students' understanding of learning material. It is hoped that this interactive learning media will make a positive contribution in improving the alphabet letter recognition skills of young children and provide a fun learning experience for them. Feasibility validation results were obtained from respondents with an average of 89.5% which was divided into 4 categories, namely the design category 90%, convenience 93%, understanding 91% and interactive 84%. Based on these results, interactive learning media for recognizing alphabet letters is included in the very feasible category and it can be concluded that interactive learning media for recognizing alphabet letters can be implemented for early childhood students with the help of teachers or independently.